Absolute beginner's guide to creating Web pages - Stauffer, Todd (Que, 2002)
Learn to create Web pages and Web sites using the latest HTML standards with this book's friendly, professional approach. Without relying on technical jargon, Absolute Beginner's Guide to Creating Web Pages serves as a hands-on tutorial for the novice. It begins by explaining the need for HTML and the basics of good Web page design. It then covers using HTML tags and tools, formatting text, adding images and building links. Later chapters demonstrate how to add features to Web pages including tables, colors, frames, multimedia content, JavaScript, Style Sheets and Dynamic HTML. The book finishes with a useful HTML command reference readers can flip to quickly while creating Web pages.